Kontribusi Dimensi-Dimensi Keadilan Organisasi dalam Memprediksi Keinginan Berpindah Pada Karyawan PT. Y - Anastasya Anastasya; Yulinda Septiani Manurung; Rianda Elvinawanty (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
The purpose of this study is to find out relationship between organizational justice and turnover intention of employees at PT. Y. The hypothesis proposed in this research stated there is a relationship between organizational justice and turnover intention of employees at PT. Y. The research data analysis used was multiple regression analysis to know the relationship between organizational justice with turnover intention. The research subjects were all employees of PT. Y consisting of 108 employees. The data were derived from a scale to measure organizational justice and turnover intention. The result of the data analysis reveal F = 24.694 with p = 0.000 (p<0,05), means there is a relationship between organizational justice with turnover intention of employees at PT. Y. The result of the study showed that the contribution (R2) was 47% (Adjusted R Square = 0,470).